A reforma da educação e a instituição do vestibular na ditadura militar brasileira: um caso de "revolução passiva"? - Lima, Marcos Eduardo Gomes de (2010)
This dissertation aims to discuss the educational counter-reform imposed by the Military Regime (1964-1985), and the meaning of the privatization of education, especially on de College Education. The research was structured around the granting of the Decree 68.908/71, that held on the vestibular exam (similar to the American SAT exam), modifying its character of test or approval exam, turning into a qualifying contest of individualist and competitive character. Besides the educational counter-reform for the College Education, awarded by the Law 5.540/68, the Law 5.692/71, on Basic Education and the other legislative measures of the same historical period, was analyzed. The research sought to explore the reasons that led the National Constituent Assembly from 1988 to tacitly accept the Decree 68.908/71, considering this position as a case of Brazilian passive revolution in the context of political opening. In this perspective, the research seeks to discuss the consolidation and dissemination of referred model of vestibular exam in the institutions of Colleges Education in Brazil, and its economic, political and ideological linkages